Radiation Performance of Different Triangular Microstrip Patch Antenna Configuration Shapes Operating at 28 GHz - Bushra Adnan Rahman; Sattar Othman Hasan (Zanco Journal of Pure and Applied Sciences, 2022)
The radiation performance of different triangular microstrip patch antenna (TMPA) shapes such as right triangle (RTMPA), isosceles triangle (ITMPA), obtuse triangle (OTMPA), and equilateral triangle (ETMPA) operating at (28 GHz) are computed and compared using inset-fed techniques and Rogers-RT5880 substrate material of permittivity  and (h=0.15 mm) height. The directivity, gain, efficiency, bandwidth, VSWR, S11 and 2D-radiation pattern for each mentioned triangular patch shapes are computed utilizing CST and HFSS method. The computed results reveal generally that the ETMPA provide better radiation performance whereas the OTMPA displays lower antenna radiation parameter values compared to the other considered ones. In addition, the antenna parameters of ETMPA with the use of coaxial probe fed are also simulated and the results are compared to those previously achieved experimentally and theoretically by other researchers. Generally, a good agreement between mentioned antenna parameter results is displayed and reliability of those achieved by CST with inset fed techniques is clearly observed. Moreover, the overall antenna parameter obtained, respectively, with CST and HFSS techniques for inset fed ETMPA are S11 (-28.68, -20.64), VSWR (1.076,1.20), gain (5.82, 6.29) dB, directivity (6.85, 7.09) dB, bandwidth (0.452, 0.369) GHz, efficiency (78.9%, 83.2%) and with a small antenna size of about (3.88 mm3) which is most reliable for 5G technology application systems.